Ответ(ы) на вопрос:
1 способ:
[latex]x- \frac{6}{x}= -1[/latex]
[latex]x^2-6+x=0[/latex]
[latex]x^2+x-6=0[/latex]
Дискриминант:
[latex]D=b^2-4ac[/latex]
[latex]D=1^2-4*1*(-6)=1+24=25=5^2[/latex]
Корни квадратного уравнения:
[latex]x_{1,2}= \frac{-bб \sqrt{D} }{2a} [/latex]
[latex]x_{1}= \frac{-1+5 }{2}= \frac{4}{2}=2[/latex]
[latex]x_{2}= \frac{-1-5 }{2}=- \frac{6}{2}=-3[/latex]
Ответ: -3 ; 2
2 способ:
[latex]x- \frac{6}{x}= -1[/latex]
[latex]x- \frac{6}{x}= -1 |*x[/latex]
[latex]x^2-6= -x[/latex]
[latex]x^2+x-6=0[/latex]
Далее так же, как и в 1 способе
Не нашли ответ?
Похожие вопросы